NILAI SOSIAL DALAM ADAT MARGONDANG (STUDI KASUS PARSADAAN HARAHAP PORTIBI DI LABUHANBATU) - Siregar, Meiridha Utari; Dora, Nuriza (Prodi Tadris Ilmu Pengetahuan Sosial FITK UIN Sumatera Utara Medan, 2025)
This study aims to examine and understand the social values of the Margondang tradition within the Parsadaan Harahap Portibi community in Labuhanbatu, a migrant community. The primary focus of the study is the values of kinship, mutual cooperation, responsibility, and mutual respect, and their role in strengthening social relationships, strengthening cultural identity, and responding to the challenges of modernization. A qualitative case study approach was used. Data were collected through in-depth interviews, participant observation, and documentation, then analyzed using descriptive qualitative methods. The results indicate that the Margondang tradition retains strong social values and serves as a unifying force for the community in the migrant community. However, modernization presents challenges such as decreased youth participation, shifting traditional meanings, and commercialization. The community has responded by engaging the younger generation, utilizing social media, and strengthening traditional institutions such as the Martupak deliberations. This study recommends a substantial reinterpretation of tradition and the involvement of the younger generation through creative approaches to support the preservation of local culture